INCIDENCE OF ABDOMINAL TUBERCULOSIS IN CASES OF THE INTESTINAL OBSTRUCTION WITH ITS CLINICAL COURSE AND MANAGEMENT - PARAS KUMAR PANDOVE; ROMMEL SINGH MOHI; PARVEEN KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: Intestinal obstruction occurs due to the failure of passage of contents through intestine. It can be because of a mechanical or functional pathology. Main causes of intestinal obstruction may vary from country to country or among zones within a specific country. The aim of this study was to evaluate the etiology, presentation, management strategies, and patients with acute mechanical intestinal obstruction and to find incidence of abdominal tuberculosis at a tertiary care hospital in Punjab, North India. Methods: This prospective study was conducted in the Department of Surgery, Rajindra Medical College Hospital, Patiala, Punjab, India, between November 2020 and September 2022. A total of 100 patients were enrolled in our study who were diagnosed to have intestinal obstruction. Observation and Results: The most common age group affected was 21–50 years (63%). Intestinal obstruction was diagnosed with males preponderance (66%). Abdominal pain, constipation, and vomiting were the most common presenting symptoms and abdominal distension was the most common physical finding on the clinical examination. The most common radiological finding was multiple air fluid levels seen on X rays. The main cause of obstruction was Adhesions and Bands followed by Ileocecal tuberculosis. About 13% patients diagnosed with abdominal tuberculosis. Patients showed good response to anti-tubercular therapy. About 6% mortality rate was reported. Conclusion: Adhesions and bands were the main causes of acute intestinal obstruction in our region. An algorithmic diagnostic approach based on different radio investigations, biopsy, and appropriate management with a rational combination of anti-tubercular therapy can reduce the morbidity of this easily curable yet potentially lethal disease.